PENGARUH SISTEM ANTRIAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN PELAYANAN DI KANTOR DINAS KEPENDUDUKANDAN PENCATATAN SIPIL KABUPATEN SIDENRENG RAPPANG - Suciana, Suciana; Idrus, Irwan; Sampara, Nirwana (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of the queuing system and organizational culture on service satisfaction in the Population and Civil Registration Office in Sidenreng Rappang Regency. This study used quantitative research methods. Data collection techniques used are observation and questionnaires. The results of this study indicate that the queuing system and organizational culture have a positive and insignificant effect on service satisfaction at the Population and Civil Registration Office in Sidenreng Rappang Regency